Childhood education and public politics in Brazil: views and reflections - Carneiro, Maria Angela Barbato (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
The contemporary society has been through a vast number of changes that affect childhood education in the whole world, especially in Brazil. The absence of public politics that includes the education of children between zero and seven years, has been incipient. Currently, we are facing serious social problems and there is a necessity of reviewing those politics in order to avoid going against democracy, offering low quality education to the less fortunate layers of society. Therefore, the present article is not the result of a research but has its goal based on concept of politics to analyze historically the course of childhood education in Brazil, taking in consideration its challenges, and reflect which are the possible changes to be considered for the next decade.